"A time to scatter stones and a time to gather them"1: Electronic media industries concentration trends in Israel 1984–2013. Issue 2 (March 2015) - Schejter, Amit M.; Yemini, Moran
Abstract: This study takes a holistic view of the audiovisual industries in Israel and describes the trends in ownership between 1984 and 2013. Market shares in 10 industries are described: broadcast television, radio, multichannel television platforms, cable and satellite delivered channels, broadband access, mobile communications, Internet Service Providers (ISPs), search engines and news websites. The data demonstrate that the Israeli system has come full circle from a government owned and operated monopoly in both the conduit and content markets it is heading toward new forms of non-competitive structures, with the rise of vertically integrated media conglomerates and highly concentrated content delivery systems. Highlights: A holistic view of the media and telecommunications industries in Israel. Describes the trends in media ownership between 1984 and 2013. "Old media" concentration in Israel is on a gradual decline. "New media" becoming vertically integrated highly concentrated distribution system.